Is reiki or prayer effective in relieving pain during hospitalization for cesarean? A systematic review and meta-analysis of randomized controlled trials - Ferraz, Guilherme Augusto Rago; Rodrigues, Meline Rosseto Kron; Lima, Silvana Andrea Molina; Lima, Marcelo Aparecido Ferraz; Maia, Gabriela Lopes; Neto, Carlos Alberto Pilan; Omodei, Michelle Sako; Molina, Ana Cláudia; Dib, Regina El; Rudge, Marilza Vieira Cunha (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: This systematic review compared reiki and prayer with drug use for relieving pain during hospitalization for cesarean, given that the popularity of integrative medicine and spiritual healing has been incrasing. It had the aim of evaluating whether reiki or prayer is effective in relieving pain during cesarean section. DESIGN AND SETTING: Systematic review with meta-analysis conducted at Botucatu Medical School, UNESP, São Paulo, Brazil.METHODS: The following databases were searched up to March 2016: MEDLINE, Embase, LILACS and CENTRAL. Randomized controlled trials published in English or Portuguese were included in the review. Two reviewers independently screened eligible articles, extracted data and assessed the risk of bias. A GRADE table was produced to evaluate the risk of bias. RESULTS: There was evidence with a high risk of bias showing a statistically significant decrease in painscore through use of reiki and prayer, in relation to the protocol group: mean difference = -1.6 8; 95% confidence interval: -1.92 to -1.43; P < 0.00001; I2 = 92%. Furthermore, there was no statistically significant difference in heart rate or systolic or diastolic blood pressure. CONCLUSION: Evidence with a high risk of bias suggested that reiki and prayer meditation might be associated with pain reduction.